Towards zero co2 emissions from public transport: the pathway to the decarbonization of the portuguese urban bus fleet - Ribeiro, Paulo (2022)
The emission of GHG has been steadily increasing in the last few decades, largely facilitated by the transport sector, which has been responsible for more than two-thirds of the manmade emissions in Europe. In cities, one of the possible solutions to decrease the emissions from fossil fuel engines is to replace vehicles with electric ones. This solution can be applied to the urban public fleet, namely by replacing urban buses with electric vehicles. Thus, this research work focuses on the Portuguese case study, which serves as an example of achieving zero CO2 emissions from buses by 2034. This timeframe of replacing the current bus fleet, mostly powered by fossil fuels, with a fully electric fleet is proven to bring financial, environmental, and health benefits to the population. The pathway to the decarbonization of urban public transport will unequivocally contribute directly to the accomplishment of several UN Sustainable Development Goals (SDGs), such as the promotion of affordable and clean energy and sustainable cities and communities, as well as to the increasing climate action (SDGs 7, 11, and 13, respectively). In addition, it will provide an opportunity for the replacement of existing buses that are generally less efficient than electric buses, from both an energy and an environmental point of view. As a result of the methodology, the Portuguese urban bus fleet would be totally replaced by electric buses by 2034 (83% battery-electric and 17% hydrogen-electric), which results in zero CO2 emission from this type of public transport.